Corrosion performance of TiAlVN-Ag nanocomposite coating deposited by reactive direct current magnetron sputtering - Giraldo , Francisco; Echavarría, Aida; Bejarano, Gilberto (ElSevier, 2022)
Surgical devices and tools are manufactured in AISI 420 martensitic stainless steel, due to its hardenability, adequate hardness and acceptable biocompatibility. Nevertheless, many surface modification strategies are being investigated with a view to improving this material by providing it with self-protection against the colonization of bacteria. One such strategy is the use of a TiAlVN-Ag nanocomposite coating to promote bactericidal effect in surgical devices; however, it is necessary to study the electrochemical response of such coatings to aggressive environments that simulate disinfection and sterilization processes. The aim of this work is to study the relationship between the microstructure, chemical phases and the electrochemical and corrosion response of TiAlVN-Ag coating, varying the amount of silver with the target power increase (0, 50, 70, 80 and 100 W). To study the microstructure, chemical phases, scanning and high resolution transmission electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction were used. Roughness, microhardness, residual stresses, qualitative adhesion of coatings were estimated by atomic force microscopy, Knoop indentation, profilometer and Rockwell C indentation, respectively. Electrochemical behavior and corrosion protection of coatings were studied using electrochemical impedance spectroscopy and potentiodynamic polarization. TiAlVN-Ag 50W coating showed an improvement in electrochemical behavior and in protection of the steel against corrosion and exhibiting higher hardness than that of the AISI 420 stainless steel substrates. This coating exhibited a dense microstructure and high crystallinity, indicating that the low Ag content does not affect the insulating nature of the coating matrix.

Los dispositivos y herramientas quirúrgicos se fabrican en acero inoxidable martensítico AISI 420, debido a su templabilidad, dureza adecuada y biocompatibilidad aceptable. No obstante, se están investigando numerosas estrategias de modificación de la superficie con vistas a mejorar este material dotándolo de autoprotección frente a la colonización de bacterias. Una de estas estrategias es el uso de un recubrimiento nanocompuesto de TiAlVN-Ag para promover el efecto bactericida en dispositivos quirúrgicos; sin embargo, es necesario estudiar la respuesta electroquímica de dichos recubrimientos a ambientes agresivos que simulen procesos de desinfección y esterilización. El objetivo de este trabajo es estudiar la relación entre la microestructura, las fases químicas y la respuesta electroquímica y a la corrosión del recubrimiento TiAlVN-Ag, variando la cantidad de plata con el incremento de potencia objetivo (0, 50, 70, 80 y 100 W). Para estudiar la microestructura y las fases químicas, se utilizaron la microscopía electrónica de barrido y de transmisión de alta resolución, la espectroscopia de rayos X de energía dispersiva y la difracción de rayos X. La rugosidad, la microdureza, las tensiones residuales y la adherencia cualitativa de los recubrimientos se estimaron mediante microscopía de fuerza atómica, indentación Knoop, perfilómetro e indentación Rockwell C, respectivamente. El comportamiento electroquímico y la protección contra la corrosión de los recubrimientos se estudiaron mediante espectroscopia de impedancia electroquímica y polarización potenciodinámica. El recubrimiento TiAlVN-Ag 50W mostró una mejora en el comportamiento electroquímico y en la protección del acero frente a la corrosión, exhibiendo una dureza superior a la de los sustratos de acero inoxidable AISI 420. Este recubrimiento presentaba una microestructura densa y una alta cristalinidad, lo que indica que el bajo contenido en Ag no afecta a la naturaleza aislante de la matriz del recubrimiento.
Keywords: Titanium aluminum vanadium nitride; Silver; Nanoparticle; Corrosion resistance; Electrochemical behavior; Magnetron sputtering; Coating